2022
DOI: 10.1007/s11356-021-18410-5
|View full text |Cite
|
Sign up to set email alerts
|

Occupational ocular health problems among marble workers at Shaq El Tho’ban industrial area in Egypt

Abstract: Eye health of the working population is an essential condition for productivity. Marble industry is processed at large scale at Shaq El Tho’ban area where much dust, crushed pieces of stone, and fluctuating temperatures are endangering employees’ health generally and eye health specifically. The objectives of this study were assessing the prevalence of the most common ocular health problems associated with marble industry and investigating the impact of the working environment and occupational risk factors on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…However, there were no findings in this study of injuries similar to globe rupture, lamellar laceration, or hyphema in the anterior segment. Khorshed et al reported that 47.6% of the workers in their study had experienced an ocular foreign body, and 10.8% had suffered an eye injury (25). In a study by Ezisi al., the general prevalence of work-related eye injuries was determined to be 32.0%, and of those working in stone quarries, there was a higher rate in stone processing workers (26).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…However, there were no findings in this study of injuries similar to globe rupture, lamellar laceration, or hyphema in the anterior segment. Khorshed et al reported that 47.6% of the workers in their study had experienced an ocular foreign body, and 10.8% had suffered an eye injury (25). In a study by Ezisi al., the general prevalence of work-related eye injuries was determined to be 32.0%, and of those working in stone quarries, there was a higher rate in stone processing workers (26).…”
Section: Discussionmentioning
confidence: 84%
“…Marble workers and occupational eye health İstanbul Tıp Fakültesi Dergisi • J Ist Faculty Med Of the 126 workers included in the current study, ocular disease was determined in 32 (25.4%), refraction error was recorded in 19 (15.1%), pterygium was recorded in 11 (8.7%), and amblyopia was recorded in 2 (1.6%) as a result of the examinations. In a recent study in Egypt, conjunctival hyperemia was seen most in the eye examinations in 59.6% of workers, and in another study that investigated ocular problems in stone quarry workers, pterygium was determined at the high rate of 22.0% (25,32). Similarly, in another study, pterygium, cataract, refraction error, pinguecula, and conjunctival hyperemia were predominant (19,26).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Air pollutants cause various kinds of harm to the human body (Khorshed et al 2021). Many studies have investigated the human response to exposure to air pollution.…”
Section: Introductionmentioning
confidence: 99%